Islamic Republic of Iran : 2009 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Iran. (IMF Staff Country Reports; Country Report ;, 2010)
The Islamic Republic of Iran's 2009 Article IV Consultation highlights that real GDP growth has slowed following the decline in oil prices, the non-oil fiscal position has become tighter, and banks' financial situation has weakened. The recent approval of an ambitious energy price reform by Parliament could bring significant medium- and long-term benefits by increasing economic efficiency, and would help improve the macroeconomic outlook. A reduction of energy subsidies and a significant increase of non-oil revenue are needed to improve economic efficiency and achieve a more sustainable medium-term fiscal position.